2018
DOI: 10.1016/j.energy.2018.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Controlling district heating and cooling networks to unlock flexibility: A review

Abstract: Flexibility in district heating and cooling systems (thermal networks in general) is an important means to cope with the intermittent generation of heat and electricity as the share of renewable energy sources (RES) increases. An important source of flexibility is the thermal energy storage present in district heating and cooling networks, found in the thermal inertia of buildings, storage units and the network itself. To unlock this flexibility and to use it effectively and efficiently, a suitable control str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 259 publications
(149 citation statements)
references
References 49 publications
2
147
0
Order By: Relevance
“…The omission of the building thermal flexibility from the model is expected to have a smaller influence, given the presence of seasonality in all storage SoC profiles, even for the solution with the highest share of primary energy import. Still, it would be interesting to see if the possibility of using the already available sources of energy flexibility (see Vandermeulen et al [37,38] for a comprehensive discussion of this topic) in thermal networks would influence the design choices made.…”
Section: Discussionmentioning
confidence: 99%
“…The omission of the building thermal flexibility from the model is expected to have a smaller influence, given the presence of seasonality in all storage SoC profiles, even for the solution with the highest share of primary energy import. Still, it would be interesting to see if the possibility of using the already available sources of energy flexibility (see Vandermeulen et al [37,38] for a comprehensive discussion of this topic) in thermal networks would influence the design choices made.…”
Section: Discussionmentioning
confidence: 99%
“…The work in [36] describes a decision support system based on a short-term optimal predictive control law considering the network's lifetime consumption. Comprehensive reviews of the most recent studies in control and optimisation for DHC systems can be found in [37,38], whereas the available software for production planning can be found in [39,40].…”
Section: Current Control Approaches In Dhc Systemsmentioning
confidence: 99%
“…The control of district heating and cooling networks has a big impact on the operation and efficiency of a district energy system. Especially for the integration of renewable energies into conventional heating and cooling networks as well as into 4th generation heating and cooling networks (Lund et al, 2014), the control of these networks is important because generation and demand are temporally decoupled (Vandermeulen et al, 2018). Since these control strategies and the resulting network operations are becoming increasingly complex, dynamic system models are important for developing and testing these strategies.…”
Section: Control Strategiesmentioning
confidence: 99%